FOREIGN MILITARY BASES IN POST-SOVIET CENTRAL ASIA - KUTNAEVA, Nuria (CENTRAL ASIA AND THE CAUCASUS, 2010)
The collapse of the bipolar system of international relations at the end of the twentieth century led to global changes in these relations, the main one being that local conflicts have replaced large-scale wars. Soft power is increasingly moving in to replace hard power; international and nongovernmental organizations, transnational companies, and even terrorist groups are taking the place of individual countries on the international arena.Nevertheless, when it comes to state security, certain mechanisms that used to be part of the bipolar system continue to function. I am referring to military bases abroad, which, in the context of globalization, continue to play just as significant role in international relations as they did during the Cold War.This article takes a look at how important it is to have these facilities in the territory of foreign states, as well as the advantages they offer the countries where they are located, using Central Asia (CA) as an example.1In this work, military bases imply “specially equipped areas used by a state for deploying its armed forces in relation to hypothetical or actual theaters of military operations.”2It must be specified that the term “military installation” should only be used in those cases when we are talking about Russia’s military presence in CA; the establishment of “military bases” is associated with other states.All empires throughout history that engaged not only in territorial expansion, but also in control over neighboring territories were known to establish their military bases in other states,3 the empire of Alexander of Macedonia, the Venetian and Genoese republics, and the colonial empires of France and England being cases in point.4